Trail making test B in postoperative delirium: a replication study - Marinus Fislage; Insa Feinkohl; Friedrich Borchers; Maria Heinrich; Tobias Pischon; Dieuwke S. Veldhuijzen; Arjen J.C. Slooter; Claudia D. Spies; Georg Winterer; Norman Zacharias (BJA Open, 2023)
Background: The Trail Making Test B (TMT-B) is indicative of cognitive flexibility and several other cognitive domains. Previous studies suggest that it might be associated with the risk of developing postoperative delirium, but evidence is limited and conflicting. We therefore aimed to replicate the association of preoperative TMT-B results with postoperative delirium. Methods: We included older adults (≥65 yr) scheduled for major surgery and without signs of dementia to participate in this binational two-centre longitudinal observational cohort study. Presurgical TMT-B scores were obtained. Delirium was assessed twice daily using validated instruments. Logistic regression was applied and the area under the receiver operating characteristic curve calculated to determine the predictive performance of TMT-B. We subsequently included covariates used in previous studies for consecutive sensitivity analyses. We further analysed the impact of outliers, missing or impaired data. Results: Data from 841 patients were included and of those, 151 (18%) developed postoperative delirium. TMT-B scores were statistically significantly associated with the incidence of postoperative delirium {odds ratio per 10-s increment 1.06 (95% confidence interval [CI] 1.02–1.09), P=0.001}. The area under the receiver operating characteristic curve was 0.60 ([95% CI 0.55–0.64], P<0.001). The association persisted after removing 21 outliers (1.07 [95% CI 1.03–1.07], P<0.001). Impaired or missing TMT-B data (n=88) were also associated with postoperative delirium (odds ratio 2.74 [95% CI 1.71–4.35], P<0.001). Conclusions: The TMT-B was associated with postoperative delirium, but its predictive performance as a stand-alone test was low. The TMT-B alone is not suitable to predict delirium in a clinical setting. Clinical trial registration: NCT02265263. (https://clinicaltrials.gov/ct2/show/results/NCT02265263).